392 Vitamin Stability in wet pet food Formulation and Production perspective. (7th December 2018) - Belay, T; Lambrakis, L; Goodgame, S; Price, A; Kersey, J; Shields, R
Abstract: Vitamins are organic elements that are essential for physiological functions. Synthetic vitamins are added to commercial pet food with complete and balanced claims to meet the requirements established by the AAFCO. Vitamins are a group of diverse compounds that vary in their stability and susceptibility to destruction by physical and chemical agents. Vitamin stability in premixes and finished foods during storage can be affected by multiple stresses such as mixture composition, humidity, temperature, light and chemical reactions such as oxidation. Trace minerals blended with vitamins can cause redox reactions that can significantly impact the stability of vitamins. Vitamin manufacturers have made improvements in fat soluble vitamin stability, including vitamin A & D3 cross-linked beadlets and vitamin E acetate that are more stable to heat and storage compared to non-cross linked natural forms. Despite the advent of more heat stable vitamin sources, thermal processes such as extrusion and retort still have an effect on vitamins and is primarily a function of temperature, time, pH, moisture content and the presence of compounds such as sulfite and thiaminase enzyme from fish that can exacerbate thiamine losses. Thiaminase enzyme is believed to be destroyed by cooking fish to 83 ◦ C, however its effect on thiamine destruction was not effective until the fish was cooked to 121 ◦ C. Studies on the effect of extrusion and retort process on severity of vitamin stability are scarce, however, existing literatures indicate that thiamine stability is less with retort compared to extrusion process. Among twenty-two commercial cat foods that were recalled for low thiamine since 2010, seventeen of them were canned cat food and 5 extruded dry cat foods. This review will examine vitamin stability during storage, retort process and during finished product shelf life, and will also provide formulation considerations.